2006
DOI: 10.1111/j.1743-6109.2006.00153.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow‐derived mesenchymal stromal cells accelerate wound healing in the rat

Abstract: Bone marrow-derived mesenchymal stromal cells (BMSCs) are multipotential stem cells capable of differentiation into numerous cell types, including fibroblasts, cartilage, bone, muscle, and brain cells. BMSCs also secrete a large number of growth factors and cytokines that are critical to the repair of injured tissues. Because of the extraordinary plasticity and the ability of syngeneic or allogeneic BMSCs to secrete tissue-repair factors, we investigated the therapeutic efficacy of BMSCs for healing of fascial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
174
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(193 citation statements)
references
References 42 publications
14
174
0
2
Order By: Relevance
“…Barbash et al (2003) found systemic delivery of MSC resulted in low levels of cells reaching the heart following MI, compared with efficient translocation of MSC to the infarcted tissue after their intra-ventricular infusion. Nevertheless, more recently, McFarlin et al (2006) demonstrated that, although the number and frequency of MSC delivery was different, fascial wound healing in rats was accelerated with a similar level of magnitude after systemic or local delivery of MSC, indicating that either mechanism of delivery is capable of conveying the beneficial effects of MSC (McFarlin et al, 2006). Successful systemic delivery of MSC is dependent upon efficient homing of the cells to the required site.…”
Section: Methods Of Therapeutic Administration Of Mscmentioning
confidence: 99%
“…Barbash et al (2003) found systemic delivery of MSC resulted in low levels of cells reaching the heart following MI, compared with efficient translocation of MSC to the infarcted tissue after their intra-ventricular infusion. Nevertheless, more recently, McFarlin et al (2006) demonstrated that, although the number and frequency of MSC delivery was different, fascial wound healing in rats was accelerated with a similar level of magnitude after systemic or local delivery of MSC, indicating that either mechanism of delivery is capable of conveying the beneficial effects of MSC (McFarlin et al, 2006). Successful systemic delivery of MSC is dependent upon efficient homing of the cells to the required site.…”
Section: Methods Of Therapeutic Administration Of Mscmentioning
confidence: 99%
“…During the proliferation periods of 1 and 7 d, the numbers of cells on all types of the fibrous matrices were found to significantly increase with an increase in the cell culturing time, which is evidenced by the cells covering most parts of the fiber mat surfaces on day 7, suggesting a good biocompatibility of these fibrous materials towards the tested cells. Quantification of Synthesized Collagen: Synthesized by mature fibroblast cells, collagen is a structural ECM protein, responsible for providing strength of various tissues 38 and also plays an important role in the haemostasis and epithelisation phase of wound healing. 39,40 The ability of AC in promoting the differentiation of fibroblasts is of prime concern in this work.…”
Section: 폴리머 제38권 제3호 2014년mentioning
confidence: 99%
“…The resulting effect provided cell proliferation, control of the extracellular matrix (ECM) deposition, and angiogenesis process. In addition to the acceleration of wound closure, the MSCs treatment strongly enhances the scar quality, which was associated to a greater quantity of collagen within the healed tissue increasing the tensile strength [13]. These cells' synthesis of larger amounts of collagen and growth factors, than native dermal fibroblasts, proves their therapeutic efficiency in cutaneous repair [14].…”
Section: Introductionmentioning
confidence: 99%